The Effect of Corporate Health Accounting Disclosure and Profitability on Firm Value with Governance as a Moderating Variable: A Quantitative Study of Healthcare Companies in Indonesia - Reinhard Stefanus; Harry Suharman; Syaiful Rahman Soenaria (LP2M IAIN Palopo, 2026)
Mental health awareness has risen as a strategic priority in the Indonesian healthcare sector post-COVID-19 pandemic, yet Corporate Health Accounting (CHA) disclosure remains minimal despite its potential to reduce employee burnout costs. This study examines the effect of CHA disclosure and profitability (ROE) on firm value (Tobin's Q), with governance as a moderating variable, in healthcare companies listed on the Indonesia Stock Exchange (IDX). Using a quantitative descriptive-verification approach with panel data regression (Eviews v14), purposive sampling yielded 14 companies (70 observations) from a population of 35 healthcare issuers listed on the IDX (2019-2023). Instruments included the GRI 403-based CHA index (scale 0-6), the OJK governance score (0-5), the ROE formula, and Tobin's Q. The results show that CHA has no significant direct (p=0.7160) or moderated (p=0.4816) effect on firm value, while profitability has a significant positive effect (p=0.00295). The conclusion emphasizes the market's preference for financial metrics over premature social disclosures, recommending improvements in the quality of CHAs and ESG regulatory mandates for long-term value creation.